METODE PERBAIKAN PERKERASAN JALAN DI KABUPATEN KATINGAN KALIMANTAN TENGAH - Novendri Agung Walen Paul Asin; Salonten Salonten; Murniati Murniati (Universitas Lambung Mangkurat, 2021)
The Hampalit – Petak Bahandang village is categorized class IIIC road, that is local roads and neighborhood roads that can be traversed by motorized vehicles including loads with a width not exceeding 2.1 meters, a length not exceeding 9 meters, and the heaviest axle load allowed is less of 8 tons. The purpose of this study is to determine the type of road damage and provide alternative ways of handling road damage. The research location is on the Hampalit – Petak Bahandang with a road length of 34,960 kilometers, with a road width of 5.00 meters, left and right shoulder width of 1.00 meters, drainage channel width of 0.30 meters and the type of existing pavement construction is HRS-Base. Type of damage that occurred there were 5 types of damage consisting of: crocodile crack (0.082 %), fine crack (0.127 %), edge crack (0.010 %), skid crack (0.006% %), hole (0.227%). The damage that occurred was dominated by hole damage with a percentage of damage 0.227%, and for total percentage of damage to the entire 34.960 kilometers road on the Hampalit – Petak Bahandang road section was 0.452 %. The method used for repairs is the 2011 Bina Marga standard repair method and has been converted using the 2018 Work Unit Price Analysis (Division 10 on Performance Maintenance Works).